Investigação da plasticidade morfológica e fenotípica de células basais e de macrófagos no epitélio prostático de ratos em diferentes microambientes hormonais - Hipácia Werneck Gomes (2020)
The basal compartment of the prostatic epithelium is composed of basal cells that, in addition to being associated with the maintenance of tissue homeostasis, may be related to the initiation and progression of prostate cancer. Basal cells of the prostate constitute a heterogeneous population, presenting several subpopulations with different structural and functional contributions to the prostate. However, little is known about the regulation of the number, morphology and function of basal cell subpopulations, as well as the influence of these cells on the changes that occur in the epithelium during the carcinogenic process. Complicating even more the understanding of the basal compartment of the prostatic epithelium, it may contain macrophages, which for many years have been confused with basal cells. The participation of macrophages in the development and progression of prostate cancer has been drawing attention, but reports regarding the presence of these immune cells in the epithelium in the tumoral context are scarce and superficial. Therefore, the aim of the present study was to investigate possible changes in the morphology and phenotype of basal cells and macrophages in the prostatic epithelium of Wistar rats in different hormonal microenvironments. For this, three experimental models were used: (1) aging, (2) induction of prostatic lesions through prolonged treatment with testosterone and estradiol and (3) castration. Immunohistochemistry and immunofluorescence assays have shown that basal cells are widely distributed in the prostate, regardless of the age of the animals, and they have varying morphology. The population of CK5-positive basal cells increased in the prostatic epithelium during aging, while the p63-positive basal cells decreased. Macrophages with varied phenotype and morphology were observed in the prostatic epithelium after surgical castration, as well as in pre-malignant and malignant lesions, either observed naturally during aging or after treatment with testosterone and estradiol. In addition, thin cytoplasmic projections of the basal cells have been observed to extend around the intraepithelial macrophages in prostatic lesions, highlighting an intimate interaction between these cells. Taken together, our results show that macrophages and basal cells are extremely plastic cells, capable of adapting their morphology and phenotype depending on the local microenvironment, playing an important role in the development and progression of prostatic lesions.